Mandarin For All: Book 2 - Yong, Ying Mei; Kang, Mei Feng (Penerbit UMP, 2017)
The course is intended for general public who wish to learn to speak Mandarin for everyday conversation purposes. The course module has been specially edited for non-native undergraduate students. The course module designed is based on the format of the Chinese Proficiency Test named as Hanyu Shuiping Kaoshi (HSK) level 2, China.